Protective effects of resveratrol on aging-induced cognitive impairment in rats - Gocmez, Semil Selcen; Gacar, Nejat; Utkan, Tijen; Gacar, Gulcin; Scarpace, Philip J.; Tumer, Nihal (Neurobiology of learning and memory, 2016)
•Aging impaired emotional and spatial learning and memory in rats.•Inflammatory cytokines were increased by aging.•Resveratrol reversed the aging impaired cognitive functions.•Resveratrol prevented elevations of inflammatory cytokines in aged rats.•Antiinflammatory effects of resveratrol can be protective for cognitive deficits in normal aging. Resveratrol, a polyphenol phytoalexine, has been shown to play a neuroprotective role in the neurodegenerative process in Alzheimer’s disease (AD) and improve memory function in dementia. However, the in vivo effect of resveratrol in normal aging models of learning and memory has not yet been evaluated. Therefore, the present neurobehavioral study was undertaken to evaluate the effect of resveratrol on cognitive impairment induced by aging in passive avoidance and Morris water maze (MWM) tests. Male Wistar albino rats were divided into four groups: young control (4month), young resveratrol (4month+RESV), old control (24month) and old resveratrol (24month+RESV). Resveratrol (50mg/kg/day) was given to the 4month+RESV and 24month+RESV groups orally for 12weeks. There was no significant difference between the groups for the first day of latency, while in aged rats, the second day of latency was significantly shortened compared to the young group in the passive avoidance test (p<0.05). Additionally, in the MWM test, the results showed a decrease in the time spent in the escape platform’s quadrant in the probe test in aged rats (p<0.05). The administration of resveratrol at 50mg/kg/day increased the retention scores in the passive avoidance test and the time spent in the escape platform’s quadrant in the MWM task (p<0.05). Furthermore resveratrol attenuated the protein levels of TNFα and IL1β in the 24-month group. These findings indicate that aging impairs emotional and spatial learning-memory and resveratrol reverses the effect of age-related learning and memory impairment. The results of this study suggest that resveratrol is effective in preventing cognitive deficit in aged rats by inhibiting the production of inflammatory cytokines.